2001
DOI: 10.1002/pen.10798
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of long‐term service performance of polymeric materials from short‐term tests: Creep and prediction of the stress shift factor of a longitudinal polymer liquid crystal

Abstract: The material studied is a longitudinal polymer liquid crystal (PLC). The creep behavior of the PLC is examined in the region of nonlinear viscoelasticity. The creep compliance D curves at nine different stress (T levels, from 10 to 50 J.cm3 at a constant temperature are determined and shifted along the log time axis for uRf = 10 J .to produce the D versus t/a, master curve. A fairly general formula for stress shift factor a , , based on free volume vf and the chain relaxation capability (CRC) derived by one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…(2) relies on an equation of state of the form v ‫ס‬ v(T,P), where T is the thermodynamic temperature and P is pressure. We have found that for all kinds of PBMs, including polymer liquid crystals (PLCs), which form a variety of phases, reliable predictions over decades of years are obtained 22,23,[25][26][27] when one uses the Hartmann equation of state 29 …”
Section: Recovery In Wear and Free Volumementioning
confidence: 99%
See 1 more Smart Citation
“…(2) relies on an equation of state of the form v ‫ס‬ v(T,P), where T is the thermodynamic temperature and P is pressure. We have found that for all kinds of PBMs, including polymer liquid crystals (PLCs), which form a variety of phases, reliable predictions over decades of years are obtained 22,23,[25][26][27] when one uses the Hartmann equation of state 29 …”
Section: Recovery In Wear and Free Volumementioning
confidence: 99%
“…9,10,[22][23][24][25][26][27] These methods rely largely on the concept of free volume v f . At higher temperatures (higher v f ) one observes at much shorter times creep and other property changes which at lower temperatures (lower v f ) would take years and decades (the time-temperature correspondence).…”
Section: Recovery In Wear and Free Volumementioning
confidence: 99%
“…In the beginning of this paper we have noted methods of prediction of service performance and service life of viscoelastic materials [6][7][8][9][10][11]. These methods cannot be applied to materials with voids.…”
Section: Article In Pressmentioning
confidence: 99%
“…Repeatedly, successful results have been obtained [9][10][11] by using the Hartmann EOS [17][18][19]. It reads…”
Section: Introduction and Key Relationsmentioning
confidence: 98%
See 1 more Smart Citation